GOVERNMENT COMMUNICATION STRATEGIES IN PUBLICIZING POLICIES, PROGRAMS, ACTIVITIES AND REGIONAL DEVELOPMENT ACHIEVEMENTS IN THE DIGITAL ERA (Case Study in The Leadership Administration Bureau of The Regional Secretariat of The Northern Sulawesi Province): STRATEGI KOMUNIKASI PEMERINTAH DALAM MEMPUBLIKASIKAN KEBIJAKAN, PROGRAM, KEGIATAN DAN CAPAIAN PEMBANGUNAN DAERAH PADA ERA DIGITAL (Studi Kasus di Biro Administrasi Pimpinan Sekretariat Daerah Provinsi Sulawesi Utara) - I Wayan Aris Wartika; Maria H. Pratiknjo; Grace Waleleng (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This research aims to analyze the government's communication strategy through the Bureau of Leadership Administration at the Regional Secretariat of North Sulawesi Province in publicizing policies, programs, activities, and regional development achievements in the digital era. The method used in this research is a descriptive qualitative method. The informants used in this study were selected using purposive sampling technique, totaling 11 people. Data collection was carried out through observation, interviews, and documentation. The research focused on planning aspects, objectives, message aspects, and media aspects. Data analysis was conducted by data reduction, data presentation, and drawing conclusions. The findings reveal that the government's communication strategy for publishing policies, programs, activities, and regional development achievements involves a systematic approach. The planning aspect consists of message preparation, design, and publication stages. The strategy primarily targets the community, aiming to provide them with government communication. The message aspect includes conveying information about upcoming and implemented policies, as well as regional development programs, activities, and achievements. The chosen media platform for publishing is Instagram, a popular social media application. In conclusion, the government's communication strategy in publicizing policies, programs, activities, and achievements of regional development in the Bureau of Administration of the Regional Secretariat of North Sulawesi Province is effective, despite relying solely on Instagram as the chosen social media platform. Therefore, it is recommended to utilize other social media platforms such as Facebook, YouTube, and others for broader reach and dissemination.